Stella's Motherhood in the Film Let Go (2024) - Faradila, Aldona (Universitas Negeri Surabaya, 2025)
Let Go (2024), a film, depicts complex motherhood through the character of Stella, a mother who experiences emotional challenges in the midst of a family on the verge of breaking apart. This study analyzed how Stella's motherhood is represented and how her motherhood influences the family relationship as a whole. Using Andrea O'Reilly's matricentric feminist approach, the study examined Stella's portrayal of motherhood through qualitative descriptive methods and film analysis, utilizing dialogue and visual elements to identify the influence of her motherhood on the family dynamic. The findings reveal that Stella's role as a mother is performed not only traditionally but also serves as an agent of transformation, creating a space for reconciliation between her husband and children. In conclusion, this study asserts that Stella’s maternal role plays a pivotal role in shaping the structure and bonds of the family in the film Let Go (2024).